Detection of bocavirus in Malaysian cats and dogs - Lee, Chee Yien (2016)
Recently, there have been an increasing number of novel groups of feline bocavirus (FBoV) and canine bocavirus (CBoV) discoveries around the world. Despite that cats and dogs are highly associated in human living environment, no study has been done to determine the presence of FBoV and CBoV in Malaysia. Thus, this study aimed to detect bocavirus in local cats and dogs in Klang Valley. Using convenience sampling method, 4 cats and 37 dogs were chosen from animal shelters. Tissue samples consisted of submandibular lymph node, lung, kidney, mesenteric lymph node, intestine, and inguinal lymph node obtained from necropsies were processed and subjected to conventional PCR using specific primers targeting the conserved nonstructural protein 1 (NS1) gene. Based on PCR analyses, 100% (4/4) and 24.3% (9/37) of cats and dogs were positive for FBoV and CBoV, respectively. Partial nucleotide sequencing of the NS1 gene were performed on 2 PCR products of FBoV and comparison of sequences were performed with published isolates. Preliminary phylogenetic analysis revealed that Malaysian FBoV isolates are distinct from reference isolates. Further study on the prevalence and pathology of FBoV and CBoV should be carried out on cats and dogs to fully understand the pathogenesis of FBoV and CBoV in the host. In conclusion, Malaysia is the fifth country to detect FBoV and CBoV.